Improving the well-being outcomes via decent work and job engagement: a findings from Persons With Disabilities (PWDs) in Malaysia - Norizan Baba Rahim; Rasidah Arshad; Zulnaidi Yaacob (Penerbit Universiti Kebangsaan Malaysia, 2024)
Implementing an appropriate improvement of existing policies, guidelines, schemes, and programmes is crucial for the organisations to solve the issue of lack of employment opportunity faced by PWDs. Building upon Psychology of Working Theory (PWT), this research tested the interaction between decent work, job engagement and well-being outcomes (meaningful work and situational well-being). Using purposive sampling technique which involved 143 PWDs in Malaysia via SurveyMonkey, the measurement items were adopted from past research with acceptable reliability, and the hypothesis were tested via Partial Least Squares (PLS) 2.0. The findings revealed that decent work was related to well-being outcomes. The association between decent work and well being outcomes was shown to be partially mediated on job engagement. This research complements the literature on human resource that contribute to the growing body of knowledge particularly regarding well-being outcomes for PWDs. The government is suggested to be attentive and revise the related policies and practices that suit the current organisational work systems and to enhance the quality and effectiveness of job support services such as Job Coach to enable the PWDs to get a job and stay in the job.